Influence of Parenting Skills on Attention and Cognitive Flexibility in Schoolchildren - Bernal-Ruiz, Francisca (2021)
Background: Although there is evidence of the effect of the contexts in which children develop on their cognitive development and executive function, there are few studies that analyze the specific influence of certain parenting skills on attention and cognitive flexibility. Objective: This study aimed to determine the influence of bonding, formative, reflective and protective parenting skills on attention and cognitive flexibility in first grade schoolchildren. Method: Ninety-six (96) dyads of fathers/ mothers/caregivers and children from Chilean schools participated in the study. The former were evaluated with the Positive Parenting Scale (e2p) and the latter with the subtests color path and gray path of the Neuropsychological Assessment of Executive Functions in Children (ENFEN). The data was analyzed using Pearson’s correlation coefficient and one-way ANOVA. Results: The results showed a major influence of formative and protective parenting skills on children’s attention. No influence of any parenting skills on cognitive flexibility was found. Conclusions: These results could be explained from a maturational point of view since the development of cognitive flexibility is modulated by the previous acquisition of other cognitive skills. Consequently, it is developed in later stages with respect to the age group of the sample.